Whole genome sequencing of macrolide resistant Streptococcus pneumoniae serotype 19A sequence type 416 - Spanelova, Petra; Jakubu, Vladislav; Malisova, Lucia; Musilek, Martin; Kozakova, Jana; Papagiannitsis, Costas C; Bitar, Ibrahim; Hrabak, Jaroslav; Pantosti, Annalisa; Del Grosso, Maria; Zemlickova, Helena (BMC microbiology, 2020)
BACKGROUND: The resistance of Streptococcus pneumoniae to macrolides is becoming an increasingly important issue and thus it is important to understand the genetics related to adaptation of this species to the widespread use of antibiotics in Europe. The 58 isolates of S. pneumoniae belonging to sequence type (ST) 416 and serotype 19A and to several different phenotypes originated from Italy, Portugal and Czech Republic were thus sequenced on Illumina MiSeq. The aim of the study was to describe genetical origine of isolates, investigate their macrolide resistance and suggest reasons for spread of ST416 in the Czech Republic. RESULTS: Investigation of genes associated with serotype determined serotype switch between 15B and 19A serotypes and core genome multilocus sequence typing (cgMLST) confirmed the origine of concerned isolates in Netherlands15B-37 clone. Inspected genomes proved variability of genes associated with the macrolide resistance even within closely genetically relative isolates. CONCLUSIONS: Participation of 19A/ST416 on the spread of Netherlands15B-37 is accompanied by serotype switch between 19A and 15B serotypes and with acquisition of genes involved in macrolide resistance to the clone that was originally macrolide susceptible. There is evident tendency to interchanging and modifications of these and surrounding genes, that could lead to accelerate spreading of this sequence type in regions with high macrolide consumption.
Keywords: sekvenování celého genomu; Multilocus Sequence Typing; séroskupina; fylogeneze; High-Throughput Nucleotide Sequencing; Pneumococcal Infections; Česká republika; Drug Resistance, Bacterial; Phylogeny; Genome, Bacterial; jednonukleotidový polymorfismus; Itálie; Phylogeography; Netherlands; Czech Republic; Nizozemsko; genom bakteriální; Polymorphism, Single Nucleotide; lidé; Humans; bakteriální léková rezistence; vysoce účinné nukleotidové sekvenování; multilokusová sekvenční typizace; fylogeografie; Streptococcus pneumoniae; Portugal; Macrolides; Serogroup; makrolidy; Italy; pneumokokové infekce; Portugalsko; Whole Genome Sequencing